1983
DOI: 10.1017/s0022112083002438
|View full text |Cite
|
Sign up to set email alerts
|

The effects of turbulence on the mean flow past square rods

Abstract: There are two main effects of turbulence on the mean flow past rods of square cross-section aligned with the approaching flow. Small-scale turbulence increases the growth rate of the shear layer, while large-scale turbulence enhances the roll-up of the shear layer. The consequences of these depend on the length of a square rod. The mean base pressure of a square rod varies considerably with turbulence intensity and scale as well as with its length.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

1986
1986
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 9 publications
3
15
0
Order By: Relevance
“…The mean drag coefficient 0.82 is in good agreement with the results reported in Norberg (1993) which gives 0Á80. Also, Deniz & Staubli (1997) gives 0Á70 but for an experiment at a higher Reynolds number, whose effect is known to produce a lower drag force due to an earlier reattachment of the shear layers (Nakamura & Ohya 1983).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean drag coefficient 0.82 is in good agreement with the results reported in Norberg (1993) which gives 0Á80. Also, Deniz & Staubli (1997) gives 0Á70 but for an experiment at a higher Reynolds number, whose effect is known to produce a lower drag force due to an earlier reattachment of the shear layers (Nakamura & Ohya 1983).…”
Section: Resultsmentioning
confidence: 99%
“…This effect was also studied in Novak & Tanaka (1974). Some of the other work is devoted to larger shape ratios (Li & Melbourne 1995;Matsumoto 2000) or to smaller ones (Nakamura & Ohya 1983, 1984Saathoff & Melbourne 1999). For large shape ratios, it was shown (Haan et al 1998) that the flow reattaches earlier when the intensity of turbulence is increased.…”
Section: A Review Of Previous Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The corresponding reduced velocities, Ur = U/ND, are 5~13 in which the approaching wind velocity (IT) is always set at 6 m/sec and the corresponding Reynolds number, Re = pUD/įi, is then controlled at 3 x 10 4 . The approaching flow fields are generated by using square mesh grids, made of wooden rods and then mounted inside the tunnel prior to the model [6,11]. Five different homogeneous turbulent flows with different turbulence intensities (T.I.)…”
Section: Wind Tunnel Facilitymentioning
confidence: 99%
“…Nakamura and Ohya [9,10] and, Nakamura and Ozono [ 11] indicated that the large turbulence scale is equivalent to the size of the entire near wake and increases the rolling-up of the shear layer. The small turbulence scale is equivalent to the thickness of the separated shear layer and increases its mixing growth rate.…”
Section: Introductionmentioning
confidence: 99%